Spray-drying Al onto hydroxide precursors to prepare LiNi0.855Co0.095Al0.05O2 as a highly stable cathode for lithium-ion batteries - Seenivasan, Manojkumar; Jeyakumar, Juliya; Jose, Rajan; Yang, Chunchen (Elsevier Ltd, 2022)
The very high specific discharge capacities of Ni> 90% cathodes are often undone by their extremely poor cycle life and thermal stability. Herein, Ni-poor, and Al-rich particle with double concentration gradients is fabricated by synthesizing particles of the Ni-rich hydroxide Ni0.9Co0.1(OH)2 in a highly efficient Taylor flow (TF) reactor and then depositing Al onto their surfaces using three methods: spray-drying and conventional wet and dry chemical coating. The uniformity of the surface distribution of Al on the Ni-rich transition metal oxide cathode materials affected the overall structural and electrochemical stability. Among our three systems, the cathode material prepared with the spray-dried Al exhibited the best performance, with an initial discharge capacity of 196.9 mA h g–1 and capacity retention of 93% after 100 cycles at a rate of 1 C. It also demonstrated superior electrochemical performance at higher C-rates. For example, at 10 C, it delivered an initial discharge capacity of 134.4 mA h g–1, compared with 56.8 mA h g–1 for the Al-free LiNi0.9Co0.1O2. We attribute this enhanced electrochemical performance to the presence of Al and its uniform distribution (through spray-drying processing) on the outer layer of the active material, with the Ni and Co elements remaining mainly within the core.